Spanish public hospital waiting lists: A theoretical and empirical approach - Ana Rodríguez-Álvarez; Mayte Rosete-Rivero (Economics: The Open-Access, Open-Assessment E-Journal, 2017)
The main objective of this work is to study the effects that supply and demand factors have on waiting lists. With this aim in mind, the authors discuss a model which explains the factors that can affect the production of healthcare, demand for healthcare, and finally, the inequalities between healthcare supply and demand. This analysis proves that, due to imbalances between supply and demand, there is an excess of demand that is equal to waiting lists. This demand excess is called the waiting list function. Hence, the second part of this paper develops an empirical analysis which estimates the function for the waiting lists of Spanish Public Hospitals for the period 1996-2009. As a result of the estimation, the supply and demand factors influencing waiting lists, as well as their evolution, are determined and studied. An imbalance between supply and demand reduces the supply and increases demand resulting in the amount traded by the market being less than potential demand.
Keywords: H4; I3; 330; hospital waiting lists; Spanish public healthcare; NHS; excess demand; demand and supply factors